Microstructural characterization and wear properties of steel surface composite coating with TiC nanoparticles through GTAW arcing techniques - Paijan, Lailatul Harina; Shamsuri, Alin Qistina; Mohd Rosli, Zulkifli; Abu Bakar, Mohd Hadzley; Mamat, Mohd Fauzi; Shaharuddin, Ahmad Shihan (Microscopy Society of Malaysia, 2025)
Gas tungsten arc welding (GTAW) for surface modification is a procedure that improves the substrate surface of material, effectively improving its hardness while influencing tribological behaviors. The aim of this work is to investigate the impact of the GTAW arcing method on the wear properties and microstructures of steel surface composite coatings containing nanoparticles of titanium carbide (TiC) ceramic particles. The GTAW process was conducted at different arcing currents which were 120A, 140A and 160A with the same pulse frequency of 25 pulses per second (PPS). Microstructural characterization and wear testing were conducted using Field Emission Scanning Electron Microscopy (FESEM), and reciprocating tribometer, respectively. Findings indicate the arcing current significantly affects the microstructural regarding the composite coating with varying concentrations of the TiC nanoparticle’s structure. The best result for Vickers microhardness value using current 140A was found to be 367.21 Hv, while the lowest result of current using 120A with 265.42 Hv. This is due to the high population of TiC nanoparticles in the composite coating. The lowest wear rate was observed for the current at 140A with a value of 7.8 x 10-6mm3/Nm. These results demonstrate the increment of hardness resulting in the improvement of wear properties. The optimum arcing current of 140A for GTAW arcing of type-2205 duplex stainless steel for surface modification can be recommended for wear industrial applications.